Plasma Viscosity : A Risk Factor In Hypertension - Puniyani R. R; Khobragade Y. S; Jaiswal V. S (Wolters Kluwer Medknow Publications, 1989)
Haemorrheological study on hypertension was done at Indian Institute of Technology Hospital, Bombay. Male population in the age groups of 35 to 60 years was screened for hypertension from February 1986 to February 1987. Out of 340 subjects examined, 44 hypertensive cases were found, who were investigated for blood viscosity profile and were compared with 45 controls. The parameters studied were plasma viscosity, whole blood viscosity, red cell aggregation, red cell deformability and haematocrit W.H.O. criteria of hypertension (HT) was strictly adhered to (B.P. above 160/95 mm of Hg). When compared to control group, plasma viscosity and whole blood viscosity were elevated in freshly detected and uncontrolled hypertensives. Red cell aggregation and deformability were significantly altered in chronic hypertensives than in normal, but haematocrit was not affected in any group.